Data-Driven Decision Making in Requirements Engineering: How Simulated Data Can Be Used for Data-Driven Requirement Validation and Elicitation - Bergrahm, Axel; Johansson, Oscar (My University, 2020)
Requirements engineering is a discipline that is exploring the opportunities in becoming data-driven. Since requirements engineering is a decision-rich field, it is drawing inspiration from the activities of data-driven decision making. The activities make use of data in different regards to improve the activities conducted within requirements engineering. This thesis makes use of simulated data from industry and investigates which factors that are important for improving decisions for requirements engineering. To achieve this, a method for data-driven requirements engineering is developed and is used as a catalyst for deriving these factors. The result shows a set of important factors to consider making data driven requirements validation and elicitation
Keywords: Requirements Engineering; Data-Driven Decision Making; Visualization; Data-Driven Requirement Engineering